Real-World Evidence for Risk Factors of Bruises and Fractures from Falls in Patients with Overactive Bladder: A Medical Record Analysis - Shigero Miyajima; Taisei Omaru; Tatsu Ishii; Hisatomi Arima; Yozo Shibata; Teruaki Izaki; Nobuhiro Haga (International Journal of Clinical Practice)
Aim. To identify the risk factors for bruises and fractures from falls in patients with overactive bladder (OAB). Methods. We evaluated 1136 patients with OAB and aged ≥50 years who visited our hospital. Age, sex, frequency of nocturnal urination, and urinary incontinence type were investigated in the 360 eligible patients. Patients were divided into three groups: those patients without falls (no-fall group), those with fall bruises (bruise group), and those with fall fractures (fracture group). The risk factors for bruises and fractures in patients with OAB were evaluated using the logistic regression analysis. In addition, association between the bruises or fractures from falls and the behavior around urination during the night was investigated. Results. The multivariate logistic regression analysis showed that female sex (odds ratio (OR) 2.888, p = 0.030) and nocturnal urination frequency ≥3 times/night (OR vs. ≤2 times/night, 2.940; p = 0.040) were significantly associated with bruises. Nocturnal urination frequency ≥3 times/night (OR vs. ≤2 times/night, 2.835; p = 0.026) and urge incontinence (OR 3.415, p = 0.016) were significantly associated with fractures. Behavior around urination during the night was significantly associated with fractures (p = 0.009). Conclusion. In the real-world clinical setting, increasing nocturnal urination frequency is a common risk factor for bruises and fractures. Also, female sex and urge incontinence were the risk factors for bruises and fractures, respectively. OAB patients with urge incontinence would especially require aggressive intervention to prevent fractures during night-time voiding.